ANALYSIS OF EARNINGS QUALITY IN HEALTHCARE SECTOR COMPANIES LISTED ON IDX - Mimelientesa Irman; Fernando Owen; Okalesa Okalesa; Isma Dewita (Bilancia : Jurnal Ilmiah Akuntansi, 2026)
This study aims to examine the effect of Capital Structure, Profitability, Liquidity, Firm Size, and Earnings Growth on Earnings Quality in healthcare sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The population of this study consists of all healthcare sector companies listed on the Indonesia Stock Exchange from 2020 to 2024, totaling 38 companies. Meanwhile, the sample comprises 17 companies selected using the purposive sampling method. Secondary data were obtained from the Indonesia Stock Exchange. The independent variables used in this study are Capital Structure, Profitability, Liquidity, Firm Size, and Earnings Growth, while the dependent variable is Earnings Quality. The research analysis method employs descriptive analysis and several types of evaluations using SPSS and SmartPLS software. The results of this study indicate that Capital Structure has a positive but insignificant effect on Earnings Quality, Profitability has a positive but insignificant effect on Earnings Quality, Liquidity has a negative but insignificant effect on Earnings Quality, Firm Size has a negative but insignificant effect on Earnings Quality, and Earnings Growth has a positive but insignificant effect on Earnings Quality in healthcare companies listed on the Indonesia Stock Exchange during the 2020–2024 period.